Proses Pengudusan Dalam Konsep Καινὴ Κτίσις Berdasarkan 2 Korintus 5:17: Perspektif Teologi Reformed - Sudarno Bostan; Refamati Gulo (JURNAL LUXNOS, 2026)
This study is motivated by the tension experienced by the early church between the old self and the new creation, as described in 2 Corinthians 5:17. This tension is relevant to the context of contemporary Christianity, where believers face cultural challenges that affect their spiritual lives and their identity as believers. A deep understanding of the concept of καινὴ κτίσις (the new creation) is considered essential for strengthening the theological foundation and the practice of sanctification in daily life. This study aims to analyze the process of sanctification based on the concept of καινὴ κτίσις in 2 Corinthians 5:17, examine its theological implications, and provide practical guidance for the church and individuals in living out their new identity in Christ. This study employs a qualitative research method using a literature review and theological analysis. The results show that sanctification is not merely a moral change but an ontological transformation involving the synergy of God’s grace and human responsibility. The new creation leads each individual to a Christ-centered life, builds spiritual identity, and enables witness within the community of faith. Furthermore, the concept of καινὴ κτίσις serves as the theological and practical foundation for the process of sanctification, emphasizing the importance of teaching, spiritual discipline, and communal life as means of spiritual growth. This study contributes to clarifying the relationship between a new identity and the daily practice of Christianity, while offering a paradigm for sustainable living in Christ.